The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1159/000153244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Conjugated Linoleic Acid in Advanced Experimental Polycystic Kidney Disease

Abstract: Background/Aims: Several dietary interventions, including those involving conjugated linoleic acid (CLA), slow progression of polycystic kidney disease (PKD) when initiated in the early stages of disease in Han:SPRD-cy rats. However, in humans, kidney disease is often undetected until extensive renal injury has developed. The objective of this study therefore was to determine whether initiating dietary CLA intervention in advanced PKD would slow disease progression. Methods: Adult male Han:SPRD-cy rats with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…serum urea, serum creatinine, creatinine clearance, proteinuria, etc.) . More recently, in obese fa/fa Zucker rats with an advanced form of renal disease, Zhan et al.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…serum urea, serum creatinine, creatinine clearance, proteinuria, etc.) . More recently, in obese fa/fa Zucker rats with an advanced form of renal disease, Zhan et al.…”
Section: Introductionmentioning
confidence: 97%
“…serum urea, serum creatinine, creatinine clearance, proteinuria, etc.) [11]. More recently, in obese fa/fa Zucker rats with an advanced form of renal disease, Zhan et al confirmed that supplementation with c9,t11 CLA did not improve advanced obesity-associated nephropathy and t10,c12 CLA worsened the renal pathology in the final stages of the diseases [12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In autoimmune NZB/W F1 mice, CLA supplementation initiated with onset of renal failure was able to slow disease progression [17]. Dietary CLA supplementation in the Han:SPRD-cy model of polycystic kidney disease reduces renal inflammation, cell proliferation, fibrosis and oxidative damage [18][19][20]. In our previous studies in the obese fa/fa Zucker rat, 8-week supplementation of young rats with t10,c12 CLA alone or in combination with the c9,t11 isomer resulted in a reduction in glomerular hypertrophy [21], which is one of the earliest signs of OAN [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%